Factors influencing consumer's preferred retail format for fresh fruits and vegetables purchase in Klang Valley, Malaysia - Gindi, Abdullahi Auwal (2016)
Several inter – linked socio – economic phenomena including urbanization, population and income growth and its associated changes in lifestyle of people, household structure, and growing young population, have dramatic impact on the way fruits and vegetables are produced, distributed, purchased and consumed. For most developing and emerging countries, including Malaysia, traditional retail formats are being strongly competed by modern retail formats especially for freshly food produce. Before the emerging of modern retail formats, the Malaysian consumers have no choice than to patronized traditional retail outlets for fresh fruits and vegetables purchases. But with the emergence of modern retail outlets in 1990s, which provides Malaysian consumers more alternatives on how and where to make fresh fruits and vegetables shopping. Alongside with this development from the consumers’ perspective, the competition within retailing in Malaysia has intensified. There is a need for the retailers as well as policy makers to have valid, accessible and practical information about consumers’ knowledge, behavior and their demand for retail formats choice for fresh fruits and vegetables purchase. This is the aim of the study of identifying attributes that influencing consumers’ retail formats choice in fresh fruits and vegetables purchase. This study considered consumers of FFV from hypermarket, supermarket, wet market, farmers market and night market. Klang Valley is the area for the study, and was clustered into six clusters. One town was chosen from each cluster and one hundred fifty respondents each were randomly selected from Kuala Lumpur and Putra Jaya and one hundred each from the remaining clusters, which makes total sample size of 700 respondents used for the study. Structured questionnaire was the instrument used for data collection and collection method was face-to-face interview. Descriptive statistics, confirmatory factor analysis, and structural equation modeling were used in analyzing the data. The demographic characteristics of the respondents include their education level, income level, marital status, ethnic groups of the respondents as well as their age groups. Majority (76%) have either College or University level of education. About 47% of the respondents earned between RM 3001 to 4000 per month and majority (54%) is within age group of 18 to 39 years. The composition of ethnic groups revealed that 63% are Malayethnic group, 26% Chinese, 6% India and 4% non-indigenous. In terms of product attributes considered by respondents, level of ripening of the FF turns out to be the most important factor for the consumers while purchasing the product (73 percent). In terms of store attributes considered by the respondents in choosing the type of retail formats for FF purchase, convenience store location turn out to be the most important factor in retail format choice (71.7 percent). Retail format preferred very much by the consumers for FFV purchase are night market, supermarket and farmers’ market. The least preferred retail formats in their ranking order are convenience store, fruits stall, wet markets and hypermarkets. For the structural models of all FF and FV retail formats choice (night market, wet market, farmers’ market, super market and hypermarket), the goodness-of-fit (GOF) measure demonstrated that all the retail format choice models have good model fit (i.e. for FF night market, χ²/df= 3.537, GFI= 0.922, AGF= 0.897, CFI= 0.944, TLI= 0.933 and RMSEA= 0.060). The results of some of the retail formats choice models support the proposed hypotheses for the FF night market model; for example choice of night market for FF purchase is significantly associated with products attributes related constructs [perceived freshness (β= 0.101), perceived quality (β= 0.09) and perceived safety (β= 0.26)]. In terms of mediation effect, the result indicates that perceived value and attitude mediate the relationships between perceived quality and retail formats choice only. But perceived value and attitude are not mediators on the relationship between freshness and safety for all the retail formats. Moderation effects of socio demographic variables were tested, and results showed the moderation effect of most of the variables. The finding of this research increases our understanding on the attributes influencing FFV consumer’s preference towards different retail formats, the relationship between the attributes and different retail format choice. This research can be used by retail mangers for assisting them to prepare effective marketing strategy. It can also be used by policy makers by increasing their insight into FFV retail formats and FFV consumers’ preferences toward such retail formats for good development of interventional policies to support and improve the welfare of both consumers and retailers.